2014
DOI: 10.1007/s10926-014-9547-0
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the EQ-5D in Patients with Traumatic Limb Injury

Abstract: The EQ-5D has sufficient construct validity, predictive validity, and responsiveness, and also provides evidence for using the utility of the EQ-5D for cost-utility analyses of patients with traumatic limb injuries in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 25 publications
1
31
0
Order By: Relevance
“…However, we found that self-care, index scores, and VAS of EQ-5D-3L showed moderate correlations with the social relationship domain of the WHOQOL-BREF (r = −0.337, −0.307, −0.356, respectively). These findings are similar to previous studies showing that small—moderate correlation existed between the index score/VAS scores of EQ-5D social relationship domain (Hung et al 2015; Konig et al 2007). The findings were somewhat different from our hypotheses.…”
Section: Discussionsupporting
confidence: 92%
“…However, we found that self-care, index scores, and VAS of EQ-5D-3L showed moderate correlations with the social relationship domain of the WHOQOL-BREF (r = −0.337, −0.307, −0.356, respectively). These findings are similar to previous studies showing that small—moderate correlation existed between the index score/VAS scores of EQ-5D social relationship domain (Hung et al 2015; Konig et al 2007). The findings were somewhat different from our hypotheses.…”
Section: Discussionsupporting
confidence: 92%
“…One of the most used instruments in trauma care is the EQ-5D. The EQ-5D is a standardized generic measure of health-related quality of life whose validity, reliability, and responsiveness have been tested in studies for other extremity morbidities [24][25][26][27][28][29][30]. We have used the EQ-6D that is an extended version of the EQ-5D questionnaire and has an additional question addressing the cognitive function [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Our study revealed the patients with BE in Taiwan had poor HRQOL in physical domain but better in environment domain. WHOQOL-BREF is a sensitive tool to evaluate HRQOL for patients with different diseases, such as diabetes mellitus [39], tuberculosis [40], lung cancer [37], inflammatory bowel disease [41], irritable bowel syndrome [42, 43], morbid obesity [30, 35, 44], epilepsy [34], heroin-dependent patients [45] and traumatic limb injury [46]. It is not only useful to compare the difference of HRQOL between cases and controls [34, 35, 38, 42] or subgroups with different severity [35] but also serves as a standard index in validation study for other disease-specific questionnaire [39, 40, 44, 46].…”
Section: Discussionmentioning
confidence: 99%